2019
DOI: 10.1016/j.immuni.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-142 Is Critical for the Homeostasis and Function of Type 1 Innate Lymphoid Cells

Abstract: Natural killer (NK) cells are cytotoxic type 1 innate lymphoid cells (ILCs) that defend against viruses and mediate anti-tumor responses, yet mechanisms controlling their development and function remain incompletely understood. We hypothesized that the abundantly expressed microRNA-142 (miR-142) is a critical regulator of type 1 ILC biology. Interleukin-15 (IL-15) signaling induced miR-142 expression, whereas global and ILC-specific miR-142-deficient mice exhibited a cell-intrinsic loss of NK cells. Death of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 59 publications
3
41
0
Order By: Relevance
“…Transfection with hsa-miR-142-5p mimic in A549 cells effectively reduced ZIKV replication, as evident from the reduced ZIKV NS5 transcript and NS1 protein levels in the presence of the mimic (Figure 6). In support of our findings, a recent report by Berrien-Elliott et al suggested miR-142 as an important anti-viral defence player that maintains homeostasis and function of type I innate lymphoid cells [48]. Given that miR-142 is enriched in hematopoietic tissue [49], this miRNA may be involved in the lineage differentiation of hematopoietic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Transfection with hsa-miR-142-5p mimic in A549 cells effectively reduced ZIKV replication, as evident from the reduced ZIKV NS5 transcript and NS1 protein levels in the presence of the mimic (Figure 6). In support of our findings, a recent report by Berrien-Elliott et al suggested miR-142 as an important anti-viral defence player that maintains homeostasis and function of type I innate lymphoid cells [48]. Given that miR-142 is enriched in hematopoietic tissue [49], this miRNA may be involved in the lineage differentiation of hematopoietic cells.…”
Section: Discussionsupporting
confidence: 89%
“…Sun et al reported that mir142 could interact with atypical E2F transcription factors to control T‐cell proliferation in graft‐vs‐host disease (GVHD) models, and Berrien‐Elliott et al found that the survival of cytotoxic type 1 innate lymphoid cells was dependent on the abundant expression of mir142. Therefore, it is not surprising that mir142 was highly expressed in highly infiltrating TMEs . Moreover, miR‐223, mir155, mir187, and mir200b have also been reported to be associated with the immune response, so it will be worthwhile to conduct more research exploring the relationships between noncoding RNAs and the immune response in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is induced by IL-15 and mediates modulation of TGFBR1. miR-142 −/− knockout mice showed increased TGF-β signaling compared to normal controls, as indicated by the augmented expression of TGFBR1 and functionally related genes in NK/ILC1 cells from spleen and bone marrow (50). Interestingly, miR-142 −/− mice presented an altered number and functionality of NK cells, with increased susceptibility to cytomegalovirus infection.…”
Section: Mir-142mentioning
confidence: 99%